An Analysis of Grammatical Errors on Undergraduate Thesis Abstract - Syaifullah Syaifullah; Helen M Sukova (ELT-Lectura, 2022)
Abstract as one of the academic genres has its own organizational framework and linguistic features. The abstract describes the important information of work or research as briefly and accurately as possible. The purpose of this research is to identify about the grammatical errors made by undergraduate students in writing of their thesis abstract in English. So, the type of this study is descriptive qualitative. In this study, the responden is the undergraduate students of Biology Department, Faculty of Education and Teachers Training, LancangKuning University in 2016. There are 43 abstracts of biology department graduated in April 2016 period. Finally, the researcher concludes that the grammatical errors found on the biological students' theses abstract, Lancan g kuning University in writing abstract are 4 errors namely_omission, addition, misformation. misordering.